2017
DOI: 10.1038/s41467-017-01682-2
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of gut microbiota and plasma bile acids enable stratification of patients for antidiabetic treatment

Abstract: Antidiabetic medication may modulate the gut microbiota and thereby alter plasma and faecal bile acid (BA) composition, which may improve metabolic health. Here we show that treatment with Acarbose, but not Glipizide, increases the ratio between primary BAs and secondary BAs and plasma levels of unconjugated BAs in treatment-naive type 2 diabetes (T2D) patients, which may beneficially affect metabolism. Acarbose increases the relative abundances of Lactobacillus and Bifidobacterium in the gut microbiota and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
358
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(404 citation statements)
references
References 59 publications
18
358
1
8
Order By: Relevance
“…Abundant evidence has demonstrated the important roles of bile acids in glucose homeostasis . Total plasma bile acid concentrations are higher in obese and T2D subjects than in healthy controls, whereas bile acid pools are also regulated by glucose‐lowering drugs such as metformin and acarbose . In the present study, we showed that saxagliptin, a DPP‐4 inhibitor, significantly increased serum concentrations of CA, GCA, GCDCA, GDCA, and GUDCA in both NW and OW/OB T2D patients, and with CDCA and DCA levels also increasing in the OW/OB group.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Abundant evidence has demonstrated the important roles of bile acids in glucose homeostasis . Total plasma bile acid concentrations are higher in obese and T2D subjects than in healthy controls, whereas bile acid pools are also regulated by glucose‐lowering drugs such as metformin and acarbose . In the present study, we showed that saxagliptin, a DPP‐4 inhibitor, significantly increased serum concentrations of CA, GCA, GCDCA, GDCA, and GUDCA in both NW and OW/OB T2D patients, and with CDCA and DCA levels also increasing in the OW/OB group.…”
Section: Discussionsupporting
confidence: 58%
“…Human studies have demonstrated that the bile acid composition in diabetic or obese patients differs from that in normal populations . Moreover, metabolic surgeries and glucose‐lowering drugs, such as metformin and acarbose, have been reported to regulate the bile acid pool contributing to glucose control . This evidence suggests that bile acids may be involved in the pathophysiological process of metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…172,173 Metformin reduced the abundance of B. fragilis in patients with type 2 diabetes and increased the concentration of bile acid glycoursodeoxycholic acid. 175 174 Similarly, acarbose is recommended for the treatment of type 2 diabetes.…”
Section: Metformin and Acarbosementioning
confidence: 99%
“…Treatment with acarbose increased the relative abundances of Lactobacillus and Bifidobacterium and reduced Bacteroides, thereby changing bile acid metabolism. 175…”
Section: Metformin and Acarbosementioning
confidence: 99%
“…Thus, the microbiota-metabolites interactions are important to maintain the host health and wellbeing. Integrative data analysis of gut microbiome and metabolome can offer deep insights on the impact of lifestyle and dietary factors on chronic and acute diseases (e.g., autoimmune diseases, inflammatory bowel disease [5] , cancers [6] , type 2 diabetes and obesity [7] , cardiovascular disorders, and non-alcoholic fatty liver disease [8] ), and provide potential diagnostic and therapeutic targets [9] .…”
Section: Introductionmentioning
confidence: 99%